Kunci Sukses melalui Edutech (Education Technology) sebagai Media Pembelajaran Kompetensi Keterampilan Bisnis dengan Aplikasi KUNCIE bagi siswa SMK Dhuafa Padang - Nadia alfitri; Tuti Azra; Humaira Humaira; Andrizal Andrizal; Yefriadi Yefriadi (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Since the pandemic two years ago, The schools have mostly conducted teaching and learning activities online. Students are provided with teaching materials in the form of documents or videos to follow the teaching materials. Of course, a cellphone is a basic requirement for students to be able to interact online with teachers. Most students as internet users use cell phones more than using laptops or internet cafes, but only for browsing, chatting with social media applications or playing online games so that it is time consuming, but not enabled for self-creativity. Therefore, an understanding is given to students so that cellphones are used optimally apart from being a formal learning medium, they are also enabled to develop their own creativity or educate themselves using digital technology by creating content that can be used as a business or online business. One of them is through the KUNCIE application, students can learn to start a business as beginners, learn from mentors who are experts in their respective fields to convey how digital-based hobbies can be used as self-potential for creativity.